Are the components of social reciprocity transdiagnostic across pediatric neurodevelopmental disorders? Evidence for common and disorder-specific social impairments. (June 2018) - Sturm, Alexandra; Rozenman, Michelle; Chang, Susanna; McGough, James J.; McCracken, James T.; Piacentini, John C.
Highlights: Social reciprocity was tested as a transdiagnostic construct in psychiatric youth. Overall, youth with autism demonstrated deficits across social domains. Social awareness deficits were found in autism and severe mood dysregulation (SMD). Significant social deficits were not observed in OCD or tic disorders. Social awareness may represent a common feature across pediatric autism and SMD. Abstract: Deficits in social communication are a core feature of autism spectrum disorder (ASD), yet significant social problems have been observed in youth with many neurodevelopmental disorders. In this preliminary investigation, we aimed to explore whether domains of social reciprocity (i.e., social communication, social cognition, social awareness, social motivation, and restricted and repetitive behaviors) represent transdiagnostic traits. These domains were compared across youth ages 7–17 with obsessive-compulsive disorder (OCD; N = 32), tic disorders (TD; N = 20), severe mood dysregulation ( N = 33) and autism spectrum disorder ( N = 35). While the ASD group was rated by parents as exhibiting the greatest social reciprocity deficits across domains, a high proportion of youth with severe mood dysregulation also exhibited pronounced deficits in social communication, cognition, and awareness. The ASD and severe mood dysregulation groups demonstrated comparable scores on the social awareness domain. In contrast, social motivation and restricted and repetitive behaviors did not appear to be transdiagnostic domains in severe mood dysregulation, OCD, or TD groups. The present work provides preliminary support that social awareness, and to a lesser extent social communication and cognition, may represent features of social reciprocity that are transdiagnostic across ASD and severe mood dysregulation.